Translation and narrative voice: translating ambiguities and narrators in Virgil’s Aeneid - Fitton-Hayward, Melanie (2020)
This thesis explores how translators recreate the narrative of Virgil’s Aeneid, a notoriously interpretable and polyvocal text characterised by its subjective and ambiguous nature. This complex narrative allows, or rather demands, interpretation from its readers and its translators. Calling on theoretical work from multiple disciplines including narratology, translation theory, and Virgilian reception, this thesis shows that the ways in which translators (re)voice narrative can reflect shifting cultural relationships with classical texts.